Association of Mitochondrial DNA Polymorphisms With Pediatric-Onset Cyclic Vomiting Syndrome - Kirana Veenin; Duangrurdee Wattanasirichaigoon; Bhoom Suktitipat; Saisuda Noojarern; Patcharee Lertrit; Thipwimol Tim-Aroon; Supannee Kaewsutthi; Suporn Treepongkaruna (Frontiers Media S.A., 2022)
BackgroundCyclic vomiting syndrome (CVS) is a functional gastrointestinal disorder characterized by recurrent stereotypic episodes of vomiting. The pathophysiology of CVS remains obscure. Previous studies have supported the hypotheses of mitochondrial dysfunction. However, data on association studies between mitochondrial DNA (mtDNA) polymorphisms and pediatric-onset CVS are limited and inconsistent. The aims of this study were to describe clinical characteristics, evaluate association of mtDNA polymorphisms 16519T and 3010A with pediatric-onset CVS and identify new mtDNA candidate variants.MethodsThis study involved Thai patients diagnosed with CVS according to the Rome III or IV criteria before the age of 15 years. Patients' demographic data, clinical characteristics, previous investigations and treatment outcomes were obtained. Blood samples were collected for next-generation (whole exome) sequencing, followed by analysis of chromosome M (mitochondrial. Variants were filtered according to clinical significance using ClinVar and MITOMAP. mtDNA polymorphisms in 148 normal Thai individuals were used as controls.ResultsForty-eight children were enrolled in the clinical study, and 30 participated in the genetic analysis. The median age at onset and median age at diagnosis was 3.0 (1.5-5.6) and 6.3 (3.0-8.6) years, respectively. Maternal history of migraine was positive in 16.7%. About 45.7% (21 of 46) of the patients achieved complete clinical remission, with the mean symptom duration of 5.9 ± 3.3 years. The prevalence of mtDNA variants 16519T and 3010A among the patient group and Thai general population (control) were as follows: 40.0% (12/30) vs. 27.7% (P = 0.18) and 6.7% (2/30) vs. 0.7% (P = 0.07), respectively. Five known pathogenic variants were identified in 6 patients, including mtDNA 8528C in one patient who also had infantile hypertrophic cardiomyopathy. Six likely pathogenic variants were found but without statistical significance. We identified 11 variants with significant prevalence in the patient group. Though, these variants were classified as variants of unknown significance (VUS), several of them were located in mt functional regions and therefore they deserve further investigations as new candidates for association with pediatric CVS.ConclusionThere were no associations of mtDNA polymorphisms 16519T and 3010A with CVS in our pediatric cohort. Five pathogenic variants and 11 VUS were found associated with pediatric-onset CVS.